Altered Ramadan fasting glycemic profiles of adults with type 1 diabetes reveal strong evidence of underestimated insulin adjustments: a 3-year observational study in Arab settings - Alguwaihes, Abdullah M.; Alyusuf, Ebtihal Y.; Alrajeh, Areej; Alotaibi, Metib; Al-Sofiani, Mohammed E. (Frontiers in Endocrinology, 2025)
BackgroundAdults with type 1 diabetes (T1D) who fast during Ramadan remain a severely understudied population in terms of changes in glycemic control, making evidence-based recommendations for insulin adjustments difficult in this age-group. To fill this gap, we aimed to prospectively observe the changes in glycemic control of young adults with T1D who fast during Ramadan.MethodsIn this 3-year prospective study, we enrolled participants with T1D with flash glucose monitoring (FGM) data during the Ramadan periods of 2020-2022. CGM data for 4 weeks before, during, and after Ramadan were collected and analyzed. A sub-cohort of age-matched non-DM participants (N=49) who fasted during the Ramadan of 2022 were included for comparison.ResultsA total of 76 participants were enrolled, of whom only 39 (19 males and 20 females, mean age 28.1 ± 8.4 years) completed the three-year follow-up. The mean duration of diabetes among these participants was 11.5 ± 8.9 years. Ten (26%) patients were on insulin pump, and 22 (56%) patients received Ramadan-focused education at baseline. Pooled glycemic trends during Ramadan showed two main abnormal glucose spikes: after Iftar (between 16:00-18:00 and 18:00-20:00), with a difference of 15.5mg/dL, and after Suhoor (between 0:00-2:00h to 4:00-6:00), with a difference of 18.8mg/dL. These abnormal glycemic indices persisted a month after Ramadan. In parallel, these glucose spikes were also observed in non-DM participants, but remained within normal limits.ConclusionsRamadan fasting among adults with T1D in SA is associated with deterioration in glycemic control, with the highest glucose spikes observed after Iftar and Suhoor. These hyperglycemic episodes were most prominent during Ramadan and persisted for at least a month after. The present real-time evidence warrants the need to review insulin adjustments in this understudied group, focusing on high risk patients with T1D, including those with history of overindulgent behavior during Ramadan.